University Lecturers’ Task-Based Language Teaching Beliefs and Practices - Huong Thi Lan Lam; Son Van Nguyen; Hong Anh Thi Nguyen (Education Sciences, 2021)
The present study aimed to investigate the beliefs and practices of task-based language teaching (TBLT) among lecturers in English as a foreign language (EFL) at technical universities in Vietnam. A total of 136 lecturers completed the questionnaire and seven of whom participated in semi-structured interviews. Findings indicated that the lecturers had positive views toward the TBLT approach and showed a willingness to use it in their classrooms, although they also shared notable challenges related to the technique. The results also showed significant differences in understanding of TBLT among lecturers with different years of experience; however, years of experience and qualifications did not affect the lecturers’ views on or implementation of TBLT. The study offers several implications for better understanding and more effectively implementing TBLT approaches in the classroom.